Streptococcus xiaochunlingii sp. nov. E24 Isolated From the Oropharynx of Healthy Chinese Children - Zou, Yang; Sun, Ye; Qi, He; Liu, Defeng; Tian, Han; Wang, Nan; Li, Xinming (Frontiers in Microbiology, 2020)
A Gram-positive, α-hemolytic, catalase-negative, facultative anaerobic and non-motile coccus was isolated form throat swabs taken from the oropharynx of healthy children. The genome was shown to be 1.950,659 bp long and contained 42.03 mol% G + C bases with 1,942 protein-coding and 53 RNA coding genes. The results of 16S rRNA gene sequencing strongly suggested that the strain is a member of the Streptococcus genus, with 98.04%, 98.11% and 97.34 % similarities to Streptococcus australis ATCC 700641T, Streptococcus rubneri LMG 27207T and Streptococcus parasanguinis ATCC 15912T, respectively. A sodA gene comparison exhibited a sequence identity of 92.6% with the closest strain Streptococcus australis ATCC 700641T. In silico DNA-DNA hybridization showed a highest DNA similarity value of 52% with Streptococcus australis ATCC 700641T. Comparing 18 biochemical traits, the similarities of the Streptococcus strain E24 were 72% with Streptococcus rubneri LMG 27207T, 78% with Streptococcus australis ATCC 700641T and 44% with Streptococcus parasanguinis ATCC 15912T. We suggest that based on the genotypic and phenotypic results that the strain E24 is a novel species of the Streptococcus genus and propose the name Streptococcus xiaochunlingii sp. nov. E24.